ORGANIZAREA LUCRĂRILOR DE OBSERVAŢII GPS PRIN METODA STATICĂ. STUDIU DE CAZ – STAŢIUNEA ARHEOLOGICĂ BUDUREASCA, JUD. PRAHOVA (PANGEEA, 2025)
Organisation of observations work GPS using static method. Case study - Budureasca Archaeological Site, Prahova County. GPS data collected for high precision applications (excluding data collected using RTK methods) must be post-processed to provide millimeter to meter level precision. Typically, the post-processing involves differential processing relative to a fixed base location. For more robust data collection methods such as static surveys, data processing in the field is not required. For many high accuracy applications final data processing in the field is not possible. A common process is to field process data as a quick quality check, then spend more time back in the office to rigorously develop the final results.